Column Web Compression Strength at End-Plate Connections - Hendrick, Alan; Murray, Thomas M. (Engineering Journal, 1984)
Current North American specifications provide design criteria to prevent local failure of H-shaped columns when flanges or moment connection plates are welded to the column flange. This design criterion was developed strictly for these types of connections. Application of these criteria when bolted end-plate connections are used for welded and welded-bolted connections. Unnecessary use of column stiffeners may result in opposite beam flanges being tensioned. Installation of column stiffeners is expensive and stiffeners can interfere with weak axis framing into the column. If stiffeners between the flanges of H-shaped columns can be eliminated, the fabrication process is greatly simplified.